STATISTICAL EVALUATION OF A FULL FACTORIAL EXPERIMENT ON DUST SUPPRESSION SYSTEMS IN PRIMARY COTTON PROCESSING FACILITIES - Tursunov, Ahror (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article explores the development and implementation of a mechatronic system designed to control the concentration of dust particles generated in cotton processing enterprises. The primary objective of the system is to extinguish dust particles after the primary cleaning device by spraying water onto them, thus reducing their dispersion into the environment. A mechatronic module is employed to monitor the concentration of dusty air in the working zone and automatically regulate the concentration of fine dust particles emitted from the cyclone. The compact size of the mechatronic module enables its deployment in isolated areas within the enterprise premises. Control of the water spray system is achieved through digital input pins connected to switches, operating based on predefined algorithms. Specially developed algorithms govern the activation or deactivation of switches in response to variations in dust particle concentration. When the concentration exceeds a predetermined threshold, the switches are activated to initiate the extinguishing process for small dust particles. This automated approach ensures efficient and timely mitigation of dust concentration, contributing to a safer and healthier working environment within cotton processing facilities.